POLITICAL ECONOMICS MEDIA: AT THE BANTEN SELECTION OF 2011 BY RADAR BANTEN AND BARAYA TV - Priatna, Ahmad Nashrudin (Universitas Muhammadiyah Surakarta, 2017)
The mass media, whether print or broadcast (TV and Radio) plays a significant role in disseminating important messages to the public / society. Karl Marx said